Pengaruh Kualitas Pelayanan Terhadap Keputusan Pembelian pada PT Zpay Komunika (Jurnal Riset Manajemen dan Akuntansi, 2025)
This study aims to determine whether there is an influence of service quality on purchasing decisions at PT Zpay Komunika. To determine how much influence service quality has on purchasing decisions at PT Zpay Komunika. Method research used is method quantitative research with the number respondents as many as 50 people . Results data analysis shows that The calculated t value for the variable. The calculated t value is 10.066>2.054 so it can be concluded that Ha is accepted and service quality has an effect on the purchasing decision variable. Based on the Adjusted R Square value of 0.672. This shows that the Service Quality variable can influence purchasing decisions by 67.2%.